Semi-solid processing of porous magnesium using Titanium Wire Space Holder (TWSH) for biodegradable bone scaffold application - Irza, Sukmana (AIP Publishing, 2023)
Porous magnesium is one of the materials that can be used as a bulk bone implant (Scaffold) because it can be used in human body tissues and is biodegradable, non-toxic and resembles natural bones. The shape of the pore in magnesium with interconnections that resemble the original bone is a challenge in the manufacture of porous magnesium for bone scaffold material. Therefore, research activities to make porous magnesium using Titanium Wire Space Holder (TWSH) with a semi-solid process to produce bone scaffold material that is biodegradable. The process carried out in this study is to compact and sinter the powder magnesium material with titanium wire using a squeeze casting tool in a semi-solid process, then dissolved using a solution of hydro fluoride acid to form porous magnesium. The tests performed are corrosion rate, density and porosity, hardness and SEM-EDX. This study succeeded in fabricating porous magnesium, which has the potential to be a bone scaffold material where the variation of the test material that approaches bone properties is a specimen with a sintering temperature of 570 °C with composition of Ti:Mg=2:3.